Short term traffic forecasting based on hybrid of firefly algorithm and least squares support vector machine - Yusof, Yuhanis; Ahmad, Farzana Kabir; Kamaruddin, Siti Sakira; Omar, Mohd Hasbullah; Mohamed, Athraa Jasim (Springer Singapore, 2015)
The goal of an active traffic management is to manage congestion based on current and predicted traffic conditions.This can be achieved by utilizing traffic historical data to forecast the traffic flow which later supports travellers for a better journey planning.In this study, a new method that integrates Firefly algorithm (FA) with Least Squares Support Vector Machine (LSSVM) is proposed for short term traffic speed forecasting, which is later termed as FA-LSSVM.In particular, the Firefly algorithm which has the advantage in global search is used to optimize the hyper-parameters of LSSVM for efficient data training. Experimental result indicates that the proposed FA-LSSVM generates lower error rate and a higher accuracy compared to a non-optimized LSSVM.Such a scenario indicates that FA-LSSVM would be a competitor method in the area of time series forecasting.